If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -7(-6x + 8) = 169 Reorder the terms: 3x + -7(8 + -6x) = 169 3x + (8 * -7 + -6x * -7) = 169 3x + (-56 + 42x) = 169 Reorder the terms: -56 + 3x + 42x = 169 Combine like terms: 3x + 42x = 45x -56 + 45x = 169 Solving -56 + 45x = 169 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '56' to each side of the equation. -56 + 56 + 45x = 169 + 56 Combine like terms: -56 + 56 = 0 0 + 45x = 169 + 56 45x = 169 + 56 Combine like terms: 169 + 56 = 225 45x = 225 Divide each side by '45'. x = 5 Simplifying x = 5
| 9x-4=2(8x+4x)+7 | | 2y^2-y^2=1 | | -7x-4(-2x-18)=80 | | 6x-4(-6x+17)=142 | | -14=-4+5u | | 4x-3(-x-2)=69 | | 2y^2+y=1+y+y^2 | | 5x+2(4x-6)=92 | | 1+-3f=4 | | 7=(3+b)4 | | 6(k-4)-8=9k+7 | | 3-9x=-7(x+5) | | 3x+7(3x-12)=132 | | -1=2w+5 | | 5x+3(x-15)=35 | | 7x+3(7x-6)=150 | | 5x-3(x-5)=-3+4x+14 | | (x+6)=6(x+9) | | 3x+2(7x-6)=73 | | 9x=50000 | | 6x+3(4x-18)=162 | | 8y+12=7x+4 | | 3x+2(x+6)=67 | | 2x-3(4x+5)=-6(x-3)-1 | | y=0.15x+29 | | (5x+12)=180-3x | | 2b-34=54 | | 8=2r-2 | | 2b+3=54 | | 3(2a-6)=8(2a-3) | | 5x-0.1=0.5x-1 | | y-3=.4(x-2) |